Implementasi Peraturan Pemerintah Republik Indonesia Nomor 37 Tahun 2021 Tentang Penyelenggaraan Program Jaminan Kehilangaan Pekerjaan (Studi Pada BPJS Ketenagakerjaan Cabang Muara Bungo) - Ayu Mustika; Fajar Ifan Dolly; Ikhsan Alfarisi (Jurnal STIA Bengkulu, 2023)
The impact of the Covid-19 pandemic in Bungo Regency has resulted in many workers being laid off unilaterally by the company without any prior notification to the workers/laborers. The laid off workers/labourers have not been included by the company in the JKP program, so the laid-off workers/labourers do not benefit from the JKP program. The purpose of this study is to analyze the implementation and to find out the obstacles in the implementation of the Government Regulation of the Republic of Indonesia Number 37 of 2021 concerning the Implementation of the Job Loss Guarantee Program in Bungo Regency. The method used in this research is using a descriptive method with a qualitative approach. While the unit of analysis in this study amounted to 9 (nine) people using purposive sampling technique. Data collection techniques in this study were in the form of observation, interviews, and documentation. While the data analysis technique uses the model proposed by Miles and Huberman. The results of this study indicate that the implementation of the JKP program in Bungo Regency organized by BPJS Ketenagakerjaan Muara Bungo Branch has been running, but has not been in accordance with Government Regulation of the Republic of Indonesia Number 37 of 2021 concerning the Implementation of the Job Loss Guarantee Program. The obstacles faced in the implementation of the JKP program in Bungo Regency, namely, the lack of cooperation carried out by the BPJS Ketenagakerjaan of the Muara Bungo Branch with relevant agencies, the lack of socialization carried out by the BPJS of Employment in the Muara Bungo Branch and the lack of company awareness regarding the social security programs that were facilitated. by BPJS Manpower.